Volatility Concerns for Crypto Currency Investments in India Amid Fears of Inflation - Bhattacharjee, Sandeep; Mitra, Kaushik (Indian Journal of Research in Capital Markets, 2024)
Purpose : The burgeoning cryptocurrency market offers an extremely profitable means of generating high-returning investments in a sector that is increasingly in demand. The goal of this research study was to examine the volatility of four cryptocurrencies, Bitcoin, Ethereum, Tether, and BNB, and determine how these fluctuations affected inflation for Indian investors. Methodology : The purpose of this research study was to examine the volatility of four cryptocurrencies, Bitcoin, Ethereum, Tether, and BNB, and to determine how these fluctuations affected inflation for Indian investors (â€œCryptocurrency prices in India Today,â€ 2023). To analyze volatility margins and determine trading volumes during such periods, data were retrieved using the MS Excel function, and Bollinger Bands were generated using the R console 4.4 open access program. Findings : To analyze volatility margins and determine trade volumes at such times, Bollinger Bands were constructed using R console 4.4 open access software and data for bitcoin transactions was gathered using an MS Excel function. While Tether and BNB showed only mild volatility, Bitcoin and Ethereum were shown to be quite volatile. Practical Implications : The findings of this research paper could prove to be very useful for academicians, investors (existent and prospective), and policymakers in the present and future markets. Originality : The goal of this research was to identify safer cryptocurrencies, which is a major problem rather than just one of utility. This is one of the very few research studies that focused on examining safer cryptocurrencies to buy in the upcoming years.